Additions to known larval host plants of butterflies of the Western Ghats, India - Deepak Naik; Mohammed S. Mustak (Journal of Threatened Taxa, 2020)
We present an additional four new larval host plants of four butterfly species in three families from the southwest part of the Western Ghats region located in Dakshina Kannada District, Karnataka State.  These updated new records are in addition to the known host plants of the Western Ghats.